Length of stay and departure strategies of Semipalmated Sandpipers (Calidris pusilla) during post-breeding migration in the upper Bay of Fundy, Canada - Neima, Sarah G.; Linhart, Rebeca C.; Hamilton, Diana J.; Gratto-Trevor, Cheri L.; Paquet, Julie (Frontiers in Ecology and Evolution, 2022)
The Bay of Fundy, Canada is a critical staging area for Semipalmated Sandpipers (Calidris pusilla) during post-breeding migration. Recent range-wide population declines and changes in diet and migratory timing in the Bay of Fundy prompted a re-examination of staging ecology, including length of stay (last estimated in 1981), which is used in calculating migratory population estimates. We used radio-telemetry and the Motus Wildlife Tracking System to estimate individual length of stay and departure conditions for 159 Semipalmated Sandpipers in 2013 and 2014. Using tracking data we compared two estimation methods, minimum length of stay and mark-recapture modeling. Using minimum length of stay, the mean length of stay was approximately 21 days, an increase from the previous estimate of 15 days. Mark-recapture models suggested a much longer staging period that is inconsistent with other data. Sandpipers captured early in the staging period stayed longer on average than those captured later. Departures from the staging area were correlated with north-westerly winds, moderate to high wind speeds and low but rising atmospheric pressures. We suggest that Semipalmated Sandpipers in the Bay of Fundy are not operating on a time-selected migration schedule and instead wait for favorable weather conditions to depart, which occur more often later in the migratory period. Population trends in the Bay of Fundy should be re-evaluated in light of the increased length of stay.